THE EFFECTIVENESS OF CITRONELLA (Cymbopogon nardus) HAND SANITIZER ESSENTIAL OIL ON THE ABILITY TO INHIBIT Escherichia coli PATHOGENIC BACTERIA: THE EFFECTIVENESS OF CITRONELLA (Cymbopogon nardus) HAND SANITIZER ESSENTIAL OIL ON THE ABILITY TO INHIBIT Escherichia coli PATHOGENIC BACTERIA - Wulandari, Siti; Nailufar, Yuyun; Martuti, Sri (Jurnal Mitra Kesehatan, 2024)
Introduction : Hand sanitizer is a hand cleaner that is used as a substitute for washing hands with soap and water. Washing handsproperly and correctly will eliminate bacteria on the palms of the hands, thereby minimizing a person's exposure to diseases such asdiarrhea. Hand sanitizer with additional essential oils is useful in inhibiting bacteria. Bacteria that cause diarrhea include Escherichia coli. This research aims to determine the effectiveness of lemongrass (Cymbopogon nardus) essential oil hand sanitizeron the ability to inhibit the pathogenic bacteria Escherichia coli. Method: This research was a true experimental research. The method stages in this research included refining citronella essential oil, testing the pH of the hand sanitizer, testing the homogeneity of the hand sanitizer, and testing the inhibitory power of the citronella essential oil hand sanitizer against the pathogenic bacteria of Escherichia coli. Result: The research results showed that hand sanitizer has a pH of 6 for each formulation. The homogeneity testing of the hand sanitizer showed a homogeneous composition and no coarse grains were visible. The diameter testing of the inhibition zone showed that the average results from 4 tests were 7.75 mm in formulation I, 10 mm in formulation II, 10.75 mm in formulation III, 11 mm informulation IV, and 14.75 mm in formulation V. Conclusion: Hand sanitizer formulations 1 (negative control) and2 (3%) have inhibition zone results that are classified as intermediate, which indicates that the preparation is less effective in inhibiting Escherichia coli bacteria. While formulation 3 (6%), 4 ( 9%), and 5 (positive control) had inhibition zone results that were classified as sensitive, indicating that the preparation was effective in inhibiting Escherchia coli bacteria.